Evaluating the effects of calcium supplementation for chicken embryos cultured in a novel biomimetic transparent eggshell - Ng, Sze Xian (Nanyang Technological University, 2023)
The chicken embryo model has long been touted as an attractive alternative for research due to its high growth rate, ease of manipulation, and logistical advantages. There are two primary techniques associated with this model; in-ovo and ex-ovo culture. The in-ovo culture is a method that allows the observation of the embryo through a small window, but poses challenges such as poor visibility, limited embryonic accessibility, and lengthy preparation time. Conversely, the ex-ovo culture functions by cultivating the embryo outside the shell. This addresses some issues highlighted above, but presents new hurdles such as poor viability and sustainability due to a lack of a calcemic eggshell and an unnatural environment. As such, this study aims to optimize ex-ovo culturing for chicken embryos by introducing the usage of a novel biomimetic, transparent polydimethylsiloxane eggshell coupled with calcium supplementation. This polydimethylsiloxane system enables a high degree of optical clarity in a three-dimensional state and retains an elliptical geometry of an egg. Benefits of utilizing such an approach can include enhanced visibility, improved accessibility, as well as overall design robustness. Alongside utilizing eggshell powder as a calcium supplement, the amount and timing of this addition were also investigated to assess optimization strategies. As a result, it was discovered that applying eggshell powder during the earlier embryonic stages was more beneficial in terms of overall growth and viability. Enhanced viability rates were also observed for all groups supplemented with eggshell powder. Additionally, a lower calcium quantity usage was perceived to generate more favorable responses in certain key characteristic aspects. These findings suggest that an extraembryonic calcium supply regulation may be time and quantity-dependent. On this basis, the concept of timing and quantity-based calcium supplementation for chicken ex-ovo models should be considered when designing experimental goals.